A Study of Completeness and Legibility in Prescription Orders at local Tertiary Care Hospitals - Gurlingayya Nanjannavar , Dr. Anil; Kumar, Dr. Ranjeet; Sahu, Dr. Kanti (Innovative Journal of Medical and Health Sciences, 2020)
Introduction : Prescription errors account for 70% of medication errors that could potentially result in adverse effects. Prescribing errors involving decision making include a wrong choice for the patient and prescription errors in prescription writing, involve illegibility, lack of an information such as date of prescription, strength, frequency of administration, etc.[10] Since Prescription errors can be more easily determined and detected through chart review, we focused our attention on them. Methods: Cross Sectional , Non Interventional & Analytical study assessed the legibility and completeness of prescriptions obtained during the study phase. The completeness of prescriptions was analyzed through the checklist of essential elements as per World Health Organization (WHO) standard guiding principles for prescription writing along with the grading system for the quality of completeness of prescriptions. Results: Total legibility percentage was 74.1% . Overall completeness was 66.8 %. very few prescription mentioned patient’s address , weight & generic names of the drugs Conclusion: Our study shows prescription errors are frequent and need to be taken care of. As these errors are easy to correct, doctors should be educated about importance of legibility of prescription, correct spelling with the correct strength and frequency ,authorized abbreviations as well as all other information on a prescription concerned with patient, prescriber and drugs to minimize the occurrence of medication errors Key Word : Prescription , Legibility , Completeness